Sądowe ustalenie ojcostwa na tle badań akt sądowych - Działyńska, Małgorzata (Wydział Prawa i Administracji UAM, 1988)
In her article, the author presents the institute of establishment of paternity in the light of empirical analyses of records of proceedings. Under examination were 238 cases closed,in years 1984-1986 in one district court operating in a large town. The research revealed that an important impulse making mothers start proceedings for regulating their children's filiation situation is the need to find material means to bring up and educate the children. Interestingly, seldom do plaintiffs raise claims concerning two non-financial issues, i.e. vesting parental authority in a father and granting a child the father's surname. Relatively frequent are in suits for establishment of paternity the defendants' declarations of voluntary recognition of paternity (48% of cases). Furthermore, judges too often urge defendants to issue such declarations. The author disapproves of the courts' practice of underestimating biological proofs, especially a serological expertise of the 2nd degree. At present such an expertise concerning HLA system is rarely performed and most often not before but after anthropological examination. The author is of the opinion that more efforts should be made to spread the application of new biological methods in filiation suits.
Suits for establishment of paternity in the light of the records of proceedings research